Bilingualism's Influence on Cognitive Development - Mohamed, Aya Mohamed Taha (Advances in Social Sciences Research Journal, 2024)
This paper explores the influence of bilingualism on cognitive development, focusing on its effects on executive functions, language processing, and auditory processing. The study examines different classifications of bilingualism and their implications for cognitive performance. Findings suggest that bilingual individuals often exhibit enhanced executive functions, such as improved attention, problem-solving, and multitasking abilities. Additionally, bilingualism may contribute to delayed onset of age-related cognitive decline. However, some challenges, including language interference and processing delays, are noted. The paper concludes by highlighting the cognitive advantages and potential limitations of bilingualism, providing insights into its role in shaping cognitive processes across the lifespan.